Hi-Tech Farms The Answer - New Straits Times, Mohd Peter Davis (2008)
THE 50 per cent increase in the international price of rice over the past two months and the possibility of further in creases unless supplies in crease Najib No plans to in 2014 crease price of local rice NST April 1 is indeed food for thought.